PENGARUH LITERASI KEUANGAN TERHADAP KINERJA USAHA PADA UMKM BATIK JUMPUTAN DI KELURAHAN TAHUNAN - Agus Dwi Cahya; Novita Sari; Titi Juliani (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2022)
The SMEs sector is one of the economic drivers, but there are many unresolved issues in its current development, one of which is related to financial sector. This research aims to investigate the influence of financial literacy toward the performance of UMKM Batik Jumputan in Tahunan, Yogyakarta. The use sample of this research is 6 respondent of UMKM Batik Jumputan in Tahunan. Data are collected using questionnaire. Prerequisite test analysis include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Methods of data analysis using simple linear regression. The result of the analysis shows that financial literacy has no significant affect on the performance of UMKM Batik Jumputan in Tahunan. While the independent variable ability of the regression model explains that dependent variable is 57,7%, while 42,3 % is explained by other variable that is not observed in this research.Key words: Financial Literacy, SMEs Performance